INFLUENCE OF ENVIRONMENTALLY FAVOURABLE BIOSTIMULATORS ON THE YIELD AND QUALITY OF FLAX (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Institute of Inorganic Chemistry o f Riga Technical University Studies on the effect o f preplant treatment of seed material with micronutrients BZn and BCu plus phytohormone Germin on the yield and quality of flax straw and flax seeds were continued using flax cultivar ‘Laura’. The yield and quality of flax straw and flax seeds increased significantly, especially under unfavourable environmental conditions. Anatomical studies on flax stems showed that the best effect on flax fibre formation was by treatment of seed material with copper borate BCu plus pytohormone Germin which resulted in a nearly uninterrupted fibre cylinder in the flax stems. Key words: Micronutrients, flax, pfytohormone, fibres.